2017
DOI: 10.1016/j.mcn.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the coatomer protein complex I in the intracellular traffic of the delta opioid receptor

Abstract: The delta opioid receptor (DOPr) is known to be mainly expressed in intracellular compartments. It remains unknown why DOPr is barely exported to the cell surface, but it seems that a substantial proportion of the immature receptor is trapped within the endoplasmic reticulum (ER) and the Golgi network. In the present study, we performed LC-MS/MS analysis to identify putative protein partners involved in the retention of DOPr. Analysis of the proteins co-immunoprecipitating with Flag-DOPr in transfected HEK293 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 40 publications
4
17
0
Order By: Relevance
“…S6 B ), thus establishing the importance of amino acids 315–324. This decamer includes KRKKIQ 313–318 , which includes two candidate motifs (KxK and KKxx) for ER retention/retrieval, a quality control step influencing the export of properly assembled protein complexes ( 21 , 22 ). Of note, two different motifs with analogous functional potentials (RWR 313–315 , RGER 322–325 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S6 B ), thus establishing the importance of amino acids 315–324. This decamer includes KRKKIQ 313–318 , which includes two candidate motifs (KxK and KKxx) for ER retention/retrieval, a quality control step influencing the export of properly assembled protein complexes ( 21 , 22 ). Of note, two different motifs with analogous functional potentials (RWR 313–315 , RGER 322–325 ; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The retention we observe likely reflects a switch in the sorting of δR between regulated export and retrieval pathways. A recent study shows that δR has sequence elements on its intracellular loops that can interact with COPI, a main mediator of retrieval, and that these interactions prevent constitutive δR surface expression ( St-Louis et al , 2017 ). Because the C-terminal tail of δR is sufficient for NGF-regulated transport, it is possible that additional biochemical mechanisms exist for signal-regulated δR transport in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as nerve growth factor (NGF), bradykinin, and δR activation itself can alter the sensitivity of neurons to δR agonists ( Patwardhan et al , 2005 ; Cahill et al , 2007 ; Bie et al , 2010 ; Mittal et al , 2013 ; Pettinger et al , 2013 ). Further, studies evaluating expression and localization of δR in cellular systems found that δR is localized to intracellular pools in neuronal cells, raising the exciting idea that the basal surface expression of δR is tightly controlled by physiological signals that regulate the surface delivery of δR ( Roth et al , 1981 ; Zhang et al , 1998 ; Petaja-Repo et al , 2000 ; Wang et al , 2001 ; Cahill et al , 2001a , b ; Bao et al , 2003 ; Kim and von Zastrow, 2003 ; Gendron et al , 2015 ; Shiwarski et al , 2017 ; St-Louis et al , 2017 ). The cellular mechanisms that regulate δR surface delivery downstream of extracellular pathways, however, are relatively unknown.…”
Section: Introductionmentioning
confidence: 99%
“…, 2014). Similarly, a lysine-based motif on the delta opioid receptor (DOR) can interact with the coatomer protein I (COPI) coat and cause retention in HEK293 cells (St-Louis et al. , 2017).…”
Section: Introductionmentioning
confidence: 99%